2020
DOI: 10.1177/1082013220935230
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different ultraviolet-C light doses on microbial reduction and the components of camel milk

Abstract: As a result of increasing interest in non-thermal technologies as a possible alternative or complementary to milk pasteurization processing, the objectives of this study were to determine the effects of different ultraviolet-C light doses on the viability of Escherichia coli O157:H7 and Salmonella enterica serovar Typhimurium and chemical changes to camel milk components. Pasteurized and inoculated camel milk samples were ultraviolet-C treated in a continuous flow system. The viability of E. coli O157:H7 and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Moreover, authors observed that the higher the number of whey passages through the UV-C apparatus, the higher the microbial reduction. Dhahir et al 2021 reported that camel milk samples subjected to the 4.15, 8.30 and 12.45 mJ/cm 2 of UV-C treatment resulted in 1.9, 3.3 and 3.9-log reductions in E. coli and 0.9, 3 and 3.9-log reductions in Salmonella typhimurium, respectively. The findings on higher bacterial reduction obtained with higher dosage are consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, authors observed that the higher the number of whey passages through the UV-C apparatus, the higher the microbial reduction. Dhahir et al 2021 reported that camel milk samples subjected to the 4.15, 8.30 and 12.45 mJ/cm 2 of UV-C treatment resulted in 1.9, 3.3 and 3.9-log reductions in E. coli and 0.9, 3 and 3.9-log reductions in Salmonella typhimurium, respectively. The findings on higher bacterial reduction obtained with higher dosage are consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Ultraviolet-C treatment can be performed under continuous or pulsed light where the liquid passes through a chamber and light photons are being absorbed by the product (Rodriguez-Gonzalez et al 2015). The UV-C spectrum has been proven to efficiently kill microorganisms in different liquids including different types of milk, while preserving nutritional and organoleptic characteristics (Dhahir et al 2021;Papademas et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Camel milk has gained attention and popularity due to its specific bioactivities, such as potential antidiabetic (Han et al, 2022) and autism prevention functionality (Deshwal et al, 2020). Dhahir et al (2020b) 1.…”
Section: Uv-c Treatment For Camel Milkmentioning
confidence: 99%
“…Dhahir et al. (2020b) investigated the effects of UV‐C dosage on the viability of E. coli O157:H7 and S. Typhimurium and changes to camel milk components and found that UV‐C treatment at 12.45 mJ/cm 2 resulted in a 3.9 log reduction in E. coli and S. Typhimurium , and this dosage did not change the main protein profile or induce lipid oxidization, as determined by secondary lipid peroxidation products.…”
Section: Fundamentals and Developments Of Nonthermal Milk Processingmentioning
confidence: 99%